MULTIPLE ORIGINS OF METHANE IN THE EARTH - Schoell M. (My University, 1988)
Methane occurrences in the Earth's crust are predominantly of biogenic origin, i.e. their ultimate source is biologically formed organic matter. Methane can also form through inorganic reactions and is consequently termed abiogenic. Biogenic methanes can either form through bacterial or thermogenic processes. Bacterial processes follow a CO2 reduction and/or fermentation pathway. The fermentation processes are quantitatively more important in recent fresh sediments and swamps. Methane formed by CO2 reduction, however, is most common in older sediments and commercial gasfields. Temperature, organic substrate and age may be the major factors controlling the relative importance of the two pathways. Stable-isotope concentrations in thermogenic methanes seem to be controlled by the extent of conversion of organic matter, the timing of gas expulsion, and trapping. The different character of methane in individual sedimentary basins may be a result of the geologic history. Geothermal methanes are most likely derived from pyrolysis of organic matter. Abiogenic methane occurs in hydrothermal vents and ophiolite complexes. Inorganic reactions, either surficial or deep-seated, are the likely source of such methanes. A uniform mantle origin of methane is not supported by the observed isotope variations in naturally occurring methanes.